2014
DOI: 10.3233/jpd-130326
|View full text |Cite
|
Sign up to set email alerts
|

Sudomotor and Cardiovascular Dysfunction in Patients with Early Untreated Parkinson's Disease

Abstract: BACKGROUND: According to Braak staging of Parkinson's disease (PD), detection of autonomic dysfunction would help with early diagnosis of PD. OBJECTIVE: To determine whether the autonomic nervous system is involved in the early stage of PD, we evaluated cardiovascular and sudomotor function in early untreated PD patients. METHODS: Orthostatic blood pressure regulation, heart rate variability, skin vasomotor function, and palmar sympathetic sweat responses were examined in 50 early untreated PD patients and 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The proposed early involvement of postganglionic cardiac autonomic nerves in PD, and the simplicity of assessing HRV, suggests potential value as a screening tool for prodromal PD. Several studies have demonstrated reduced HRV in early PD . Furthermore, we and others have described significantly reduced HRV in idiopathic rapid eye movement (REM) sleep behavior disorder .…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The proposed early involvement of postganglionic cardiac autonomic nerves in PD, and the simplicity of assessing HRV, suggests potential value as a screening tool for prodromal PD. Several studies have demonstrated reduced HRV in early PD . Furthermore, we and others have described significantly reduced HRV in idiopathic rapid eye movement (REM) sleep behavior disorder .…”
mentioning
confidence: 69%
“…Several studies have demonstrated reduced HRV in early PD. 14,15 Furthermore, we and others have described significantly reduced HRV in idiopathic rapid eye movement (REM) sleep behavior disorder. 16,17 Finally, a large prospective cohort study found decreased time domain HRV measures were associated with an increased risk of PD.…”
mentioning
confidence: 98%
“…HFms 2 . HFms 2 was reported in 24 studies [18,[20][21][22][23][24][26][27][28][29][30]35,36,39,40,45,47,48,[54][55][56]59,63,64]. The mean HFms 2 was 145.2 ± 41.1 ms 2 in PD patients and 219.4 ± 48.8 ms 2 in the healthy control group.…”
Section: Frequency-domain Parameters Of Hrvmentioning
confidence: 86%
“…However, studies in patients with early PD are scarce, and the majority of studies that have investigated dysautonomias have focused on gastrointestinal and cardiovascular symptoms. Most studies report gastrointestinal symptoms as the most common dysautonomia, and it is well known that constipation typically presents before the onset of motor symptoms [ 14 , 15 ]. Urinary symptoms were more prevalent and frequent in our cohort.…”
Section: Discussionmentioning
confidence: 99%